KAJIAN YURIDIS PENCABUTAN PASAL 66 AYAT (1) UUJN NO. 30 TAHUN 2004 OLEH MAHKAMAH KONSTITUSI (PUTUSAN MK NO. 49/PUU-X/2012) DAN KELUARNYA UU NO.2 TAHUN 2014 TENTANG PERUBAHAN UU NO.30 TAHUN 2004 TENTANG JABATAN NOTARIS - MEYATY MEYATY (PREMISE LAW JURNAL, 2015)
Article 66 paragraph (1) of Law of Notary Position No.30/2004 is a form of legal protection provided by the legislation for notary as public official. The research was a descriptive analytical normative juridical. The result of the research showed that the revocation of Article 66 paragraph (1) of Law of Notary Position No.30/2004 had the consequence of calling and examining a notary in a criminal case by the police investigators directly without getting any permission from the Notary Honorary Council. The revocation of Article 66, paragraph (1) of Law of Notary Position No. 30/2004 had caused the authority o f the Notary Honorry Council in giving the lisence in a written form the investigators and judges in the process of calling and examining the crimninal case which had been revoked its authority. The enactment of Law of Notary Position No: 2/2014 containing legal protection for the notaries who are called and examined in a criminal case has not been able to be implemented yet because the Notary Honorary Council with authority in giving permission to call and examine a notary in a criminal case has not been established. Keywords: Legal Protection, Notary, Law of Notary Position No.30/2004, Law of Notary Position No: 2/2014